SOME PECULIARITIES OF TECHNOLOGY AND ORGANIZATION OF ALUMINIUM AND ITS ALLOYS RECYCLING - A. M. Galushko; S. P. Korolev; V. L. Tribushevskij; V. M. Mihailovskij; L. V. Tribushevskij; A. G. Sheshko; M. S. Korolev (Литьë и металлургия, 2010)
Some peculiarities of technology and organization of recycling of aluminium and its alloys are examined. Analysis of peculiarities of the melting technology in rotor furnace and organization of aluminium and its alloys recycling shows that modern production provides high efficiency of the process, ensuring high quality of alloys.